The characteristics of dysphagia and the incidence of pneumonia in Myotonic dystrophy type 1 patients especially concerning swallowing function evaluated by endoscopy. Issue 6 (December 2022) - Kambayashi, Tomonori; Hirano-Kawamoto, Ai; Takahashi, Toshiaki; Taniguchi, Sayaka; Yoshioka, Masaru; Tanaka, Hiroyasu; Oizumi, Hideki; Totsune, Tomoko; Oshiro, Saki; Baba, Toru; Takeda, Atsushi; Hisaoka, Takuma; et al.
Abstract: Objective: The objectives of the study were to clarify the characteristics of dysphagia and the incidence of pneumonia in Myotonic dystrophy type 1 (DM1) patients, and to investigate the relationship between the development of pneumonia and the DM1 patient's background, especially concerning swallowing function evaluated by endoscopy. Methods: The subjects were 88 DM1 patients who underwent swallowing function evaluation. The severity of disease in DM1patients was assessed based on the muscular impairment rating scale (MIRS), and the number of CTG repeats. Patients were divided into two groups; those who developed aspiration pneumonia within two years after swallowing assessment and those who did not develop aspiration pneumonia. Swallowing function was assessed using the food intake level scale (FILS), repetitive saliva swallowing test (RSST), the modified water swallowing test (MWST), and the Hyodo score. Results: Onset of pneumonia within two years of assessment was observed in 22 cases (25%). Age, FILS, and Hyodo score were significantly different between pneumonia and non-pneumonia groups. There was a significant difference in swallowing function tests such as FILS, RSST, and Hyodo score between males and females. The Hyodo score cutoff value for predicting pneumonia within two years was determined by ROC analysis. A cutoff value of 6 was found to have a sensitivity of 0.545 and a specificity of 0.833 (area under the curve=0.722). Conclusion: It is important to evaluate the swallowing function of DM1 patients by endoscopy to prevent aspiration pneumonia. In addition, male patients are more likely to deteriorate in swallowing function and should be carefully monitored.